2015
DOI: 10.1302/0301-620x.97b3.33242
|View full text |Cite
|
Sign up to set email alerts
|

Early surveillance of ceramic-on-metal total hip arthroplasty

Abstract: Ceramic-on-metal (CoM) is a relatively new bearing combination for total hip arthroplasty (THA) with few reported outcomes. A total of 287 CoM THAs were carried out in 271 patients (mean age 55.6 years (20 to 77), 150 THAs in female patients, 137 in male) under the care of a single surgeon between October 2007 and October 2009. With the issues surrounding metal-on-metal bearings the decision was taken to review these patients between March and November 2011, at a mean follow-up of 34 months (23 to 45) and to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
2
22
0
1
Order By: Relevance
“…Yi et al [7] and Hill et al [3] recently reported their results determining metal ion concentrations following CoM THA with a mean follow-up of 50 and 34 months, respectively (Table 2). Like in the current series, the serum levels of Co and Cr were significantly elevated compared to normal values without stabilization or downward trend after a running in period of the tribological bearing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yi et al [7] and Hill et al [3] recently reported their results determining metal ion concentrations following CoM THA with a mean follow-up of 50 and 34 months, respectively (Table 2). Like in the current series, the serum levels of Co and Cr were significantly elevated compared to normal values without stabilization or downward trend after a running in period of the tribological bearing.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrahigh crosslinked polyethylene and ceramic-on-ceramic (CoC) bearings are known to perform very well [2, 3]. Nevertheless, hard-on-hard bearings for THA continue to be in the focus of attention, especially due to the increasing number of revision surgeries for metal-on-metal (MoM) articulations [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, while investigative studies are yet underway to assess the real extent of these potential benefits, only few published evidence by clinical reports are yet available and very little is known about the actual material response in CoM articulations when introduced in the human body . A recent review on 56 CoM hips implanted between 2008 and 2009 at a single hospital by a single surgeon showed a high early failure rate of 10.7% within a mean of 1.5 years because of femoral stem loosening caused by high frictional forces .…”
Section: Introductionmentioning
confidence: 99%